The upside of aging : how long life is changing the world of health, work, innovation, policy, and purpose - Irving, Paul H. (Wiley, 2014)
The Upside of Aging: How Long Life Is Changing the World of Health, Work, Innovation, Policy and Purpose explores a titanic shift that will alter every aspect of human existence, from the jobs we hold to the products we buy to the medical care we receive - an aging revolution underway across America and the world. Moving beyond the stereotypes of dependency and decline that have defined older age, The Upside of Aging reveals the vast opportunity and potential of this aging phenomenon, despite significant policy and societal challenges that must be addressed.